Happiness and footprints: assessing the relationship between individual well-being and carbon footprints - Daniels, P; Ambrey, C (My University, 2016)
This study investigates the nature of the empirical link between an individual’s wellbeing and their carbon footprint. It employs a novel approach matching data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, to household expenditure and greenhouse gas-based carbon footprints. The carbon footprints are calculated using environmental factor multipliers from the detailed and globally integrated multi-regional input-output (MRIO) tables provided by the Eora MRIO database. The results indicate that higher carbon footprints are associated with marginally lower levels of wellbeing. This relationship appears to be linear. Furthermore, this relationship does not differ greatly for individuals across the wellbeing distribution. The findings of this study both: (1) add to the body of knowledge on the link between carbon footprints and wellbeing; and (2) provide policy makers with evidence and strategic guidance on the wellbeing implications of mitigating carbon footprints.
Environment, Development and Sustainability
Keywords: Health -- Wellbeing; Beliefs and Values; Health and wellbeing; Identity; Health; Beliefs and Values; Wellbeing; Identity; Health and wellbeing